COMPARATIVE STUDY OF DISCUSSION AND QUESTION-ANSWER LEARNING METHOD TO IMPROVE LEARNING OUTCOMES OF VOCATIONAL HIGH SCHOOL STUDENTS - Ramdayana, Ira Pratiwi; Prasetyono, Hendro; Rahman, Nurul Viah Tsania (Jurnal PAJAR (Pendidikan dan Pengajaran), 2020)
This study aims to determine whether there are differences in learning outcomes using discussion learning methods and using the Q&A learning method at Yaperjasa Vocational High School. The type of the research was Classroom Action Research with quantitative approach using the comparative method. The number of samples was 80 students, which divided into 2 classes, namely class XI Office Administration 1 (control class) using the discussion method and class XI AP 2 (experimental class) using the question and answer method. The results of the study showed that there were 3 cycles, namely the first cycle t-value > t-table or 3.323 > 1.685, in cycle II t-value < t-table and −0.087 < 1.685, and in cycle III t-value > t-table or 3.209 > 1.685. Cycles I and III showed that t-value was greater than t-table. It meant that the values obtained by students in the control class with the experimental class there were significant differences in learning outcomes. Students’ learning outcomes by applying discussion learning methods compared to using question and answer learning methods.